Design and synthesis of near-infrared fluorescence-enhancement probes for the cancer-specific enzyme hNQO1. (August 2017) - Zhang, Changyu; Zhai, Bei-Bei; Peng, Tao; Zhong, Zelin; Xu, Lianbin; Zhang, Qiang-Zhe; Li, Lu-Yuan; Yi, Long; Xi, Zhen
Abstract: Near-infrared (NIR) fluorescence-based sensors capable of selective detection of cancer biomarkers in vivo would be useful tools for early cancer detection. Two new NIR fluorescent probes were developed for detection of cancer-specific enzyme hNQO1 in colorectal cancer cells (HT29) in mice. Probe1 was based on cleavage of ester and intramolecular charge transfer (ICT) effect, which showed fast-response property toward hNQO1 for real-time enzymatic assay in vitro . Probe2 was based on cleavage of amide and photo-induced energy transfer (PET) effect, which was stable, cell-membrance-permeable, low cytotoxic, and highly selective and sensitive for hNQO1. The properties of2 enabled its use in differentiating hNQO1-positive HT29 cancer cells and hNQO1-negative human breast cancer cells in vitro and bioimaging of HT29 cells in living mice, implying that our new probe could serve as potentially efficient tools for detection of endogenous hNQO1 in living animals. Graphical abstract: Two new near-infrared fluorescent-enhanced probes1 and2 were developed for detection of hNQO1 activity in vitro and in mice.2 was successfully used in differentiating hNQO1-positive HT29 cancer cells and hNQO1-negative human breast cancer cells in vitro and bioimaging of HT29 cells in living mice.